Contribution of ergonomics and human factors to sustainable development: a systematic literature review. Issue 3 (4th March 2023) - Bolis, Ivan; Sigahi, Tiago Fonseca Albuquerque Cavalcanti; Thatcher, Andrew; Saltorato, Patrícia; Morioka, Sandra Naomi
Abstract: Although a significant amount of research has already been published, the field of ergonomics/human factors and sustainability (E/HF-S) has not yet been systematically profiled based on recent studies. Conducting a systematic review of the literature, this article aims: (i) to identify the main emergent research themes in this subject area and (ii) to provide future directions for applied research and practice on E/HF-S. Six emergent research themes were identified in this literature allowing for a proposal to synthesise the main concepts related to E/HF-S. However, it was noted that there are still relatively few empirical papers which assess the models being developed or that apply E/HF principles to sustainability challenges. Thus, this paper identifies the opportunities for practical application related to E/HF-S. The last part of the paper explores the E/HF-S opportunities using an external framework; the United Nations' sustainable development goals. Practitioner summary: The field of ergonomics/human factors and sustainability (E/HF-S) has not yet been organised by recent studies. Conducting a systematic review of the literature, this article identifies the main emergent research themes in this subject area, and it provides future direction for applied research and practice on E/HF-S. Abbreviations: ACE: activity-centred ergonomics; E/HF: ergonomics/human factors; E/HFS: ergonomics/human factors and sustainability; IEA: International Ergonomics Association; PRISMA: Preferred Reporting Items for Systematic Reviews and Meta-Analyses; SDG: Sustainable Development Goal